Board Composition And Firm Performance: A Literature Review - Muhammad Agung Prabowo (Jurnal Siasat Bisnis, 2010)
This paper discusses the empirical studies investigating the association between board composition and organizational outcome. The board composition is the most important attribute of the board institution as such a composition determines board’s characteristics, structure and process. The paper explores the motivation and contribution of previous studies that serves as a basis for defining the significance of a replication work. The paper also presents the outcome ap-proach adopted by previous works. An avenue for further research is presented in the last sec-tions.Keywords:    corporate governance, board structure, firm performance, outcome approach, specific task, financial-based performance